The Train-Bridge Coupled Vibration Analysis of a Long-Span Prestressed Concrete Continuous Beam Bridge under Creep Deformation Effect - Hao Luo; Chuyi Xu; Xianbei Gan; Mougang Liu; Xiangrong Guo; Hui Guo (Applied Sciences, 2022)
The track smoothness of high-speed railroads is severely limited to ensure train performance. The concrete continuous girder bridge is deformed to influence the smoothness of the bridge decks and track caused by creep bulge. There is a need to research the impact of beam creep on the dynamical response of bridge and train operation safety. This paper used Midas software to calculate the long-term deformation of large-span prestressed concrete continuous beam bridges under concrete creep and shrinkage. The train-bridge coupled system was established by adopting self-programming software. Thereafter, the large-term deformation results of the main girder are considered as track irregularity input into the vibration equation of the train-bridge system. The safety of the train operation was evaluated by calculating the dynamic response of the bridge and analyzing the criteria of train running safety. It was shown that the indicators of the large-span bridge are within the allowable code values under all working conditions. The bridge deformation under creep has an impact on the displacement and acceleration response of the bridge when a high-speed train passes through. There is no noticeable impact of creep deformation on the operational performance of trains. Nevertheless, the criteria for assessing the safety of trains’ operation, such as derailment factor, wheel load differences, lateral wheel forces, and vehicle acceleration, have been increased.